Prospective multicenter randomized controlled trial comparing adenoma detection rate in colonoscopy using water exchange, water immersion, and air insufflation - Hsieh, Yu-Hsi; Tseng, Chih-Wei; Hu, Chi-Tan; Koo, Malcolm; Leung, Felix W. (Gastrointestinal endoscopy, 2017)
Adenoma detection rate (ADR), defined as the proportion of patients with at least one adenoma of any size, is a quality indicator. We tested the hypothesis that water exchange (WE) improves ADR but water immersion (WI) has no adverse effect on ADR compared with air insufflation (AI). A prospective study was conducted at the Dalin Tzu Chi Hospital in southern Taiwan and the Hualien Tzu Chi Hospital in eastern Taiwan on patients randomly assigned to WE, WI, or AI with stratification by the 3 study colonoscopists. The primary outcome was ADR. From July 2013 to December 2015, 651 patients were recruited and randomized into 3 groups with a 1:1:1 ratio (217 patients per group). Overall, ADR met quality standards: WE 49.8% (95% CI, 43.2%-56.4%), AI 37.8% (95% CI, 31.6%-44.4%), and WI 40.6% (95% CI, 34.2%-47.2%). Compared with AI, WE significantly increased ADR (P = .016). There was no difference between WI and WE. ADRs of WI and AI were comparable. Compared with AI, WE confirmed a longer insertion time, higher cleanliness score, but similar adenoma per positive colonoscopy (APPC) and withdrawal time with polypectomy. Subgroup analysis found WE significantly increased ADR in propofol-sedated patients. Multivariate generalized linear mixed model analysis revealed that age ≥50 years, WE (vs AI), colonoscopy indication, no previous history of colonoscopy, and withdrawal time >8 minutes were significant predictors of increased ADR. Confirmation of prior reports showing WE, but not WI, increased ADR further strengthened the validity of our observations. WE significantly increased ADR in propofol-sedated patients. The outcome differences justify assessment of the role of WE in colorectal cancer prevention. Similar APPC and withdrawal times suggest that adequate inspection was performed on colonoscope withdrawal in each of the study arms. (Clinical trial registration number: NCT01894191.)